Perbandingan Hukum Siyasah dan Hukum Positif dalam Penyelesaian Sengketa Pilkada - Myaskur, Myaskur; Ubaidillah, Nizam (Bahasa Indonesia, 2024)
Regional Head Elections (Pilkada) often encounter disputes that impact political stability and public trust. This study compares siyasah law and positive law in resolving Pilkada disputes. Positive law, based on formal regulations, emphasizes legality and transparency through institutions like the Constitutional Court. Conversely, siyasah law, rooted in sharia principles, offers a deliberation-based approach focusing on communal welfare. The analysis reveals that positive law excels in legal certainty but lacks adaptability to local contexts, while siyasah law is more flexible but faces challenges in implementation within a plural society. This study recommends integrating both approaches to establish a more equitable, effective, and community-responsive dispute resolution mechanism for Pilkada.